2016
DOI: 10.18261/issn.1891-943x-2016-01-02
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Inquiry into Student Learning: - The TISL Heart Model and Method for use in Teachers’ Professional Development

Abstract: Researchers have recently been calling for new models of teacher education and professional development for the 21st century. Teacher inquiry, where the teacher's own practice is under investigation, can be seen both as a way to improve day-to-day teaching in the classroom and as professional development for teachers. As such, it should also have a role in teacher education. In this article, we present the iterative development of the TISL Heart, a theory-practice model and method of teacher inquiry into stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…There have been two phases to the inquiry. During the first phase, the lead teachers participated in a professional development workshop where the researchers facilitated seven teachers in the first stages of the TISL Heart method (Hansen & Wasson, 2016), the outcome of which was an inquiry question and a plan for the inquiry. Of the seven teachers, 3 were STEM teachers, and 4 teachers were language teachers (for French, Spanish, and two teachers of Norwegian to hearing impaired).…”
Section: Case 2: Teacher Inquiry Into Students' Use Of An Open Learnementioning
confidence: 99%
“…There have been two phases to the inquiry. During the first phase, the lead teachers participated in a professional development workshop where the researchers facilitated seven teachers in the first stages of the TISL Heart method (Hansen & Wasson, 2016), the outcome of which was an inquiry question and a plan for the inquiry. Of the seven teachers, 3 were STEM teachers, and 4 teachers were language teachers (for French, Spanish, and two teachers of Norwegian to hearing impaired).…”
Section: Case 2: Teacher Inquiry Into Students' Use Of An Open Learnementioning
confidence: 99%
“…Similar to the human-computer interaction method of "cognitive walkthrough" (Nielsen & Mack, 1994), educators seemed more comfortable reflecting through questions than through statements. This is aligned with the idea that the formulation of a question is key to the teacher inquiry process (see also Hansen & Wasson, 2016). • Bring in user interface/usability heuristics at a later stage only.…”
Section: Discussion Conclusion and Design Implicationsmentioning
confidence: 72%
“…Studies show that schools pay efforts to have data systems that organize and analyze interim assessment data and data warehouses with current and historical student data. Our study indicated that elements to scaffold teachers to conduct teacher-led inquiry in the technologyenriched classroom as suggested by Hansen and Wasson [2] can be better supported. In our program, the data were collected rather traditionally-tests, surveys and questionnaires, mainly, and paper-based observation sheets.…”
Section: Technology Supportmentioning
confidence: 70%
“…Focusing more on process-oriented data collection-with a variety of tools and efficient ways for classroom observations-timely access to students' learning results might influence the use of data for improving the classroom instruction. The growing use of technology as part of teachers' practice opens up the possibility for a change from researcher-centered studies to teacher-centered approaches to inquiry [2].…”
Section: Technology Supportmentioning
confidence: 99%
See 1 more Smart Citation